Psychosocial Experiences of Older Women in the Management of Urinary Incontinence: A Qualitative Study - Javanmardifard, Sorur; Gheibizadeh, Mahin; Shirazi, Fatemeh; Zarea, Kourosh; Ghodsbin, Fariba (Frontiers in Psychology, 2022)
Introduction: Urinary incontinence is a prevalent disorder amongst older women. Identifying the psychosocial experiences of older women in disease management can improve the patient care process. Hence, the present study aimed to determine the psychosocial experiences of older women in the management of urinary incontinence. Methods: This qualitative study was conducted using conventional content analysis. The study data were collected via unstructured in-depth face-to-face interviews with 22 older women suffering from urinary incontinence who were selected via purposive sampling. Sampling and data analysis were done simultaneously and were continued until data saturation. The interviews were recorded, transcribed, and analyzed using the method proposed by Graneheim and Lundman. Results: The results indicated that the older people with urinary incontinence had various psychosocial experiences while living with and managing this disease. Accordingly, four main themes were extracted from the data as follows: ‘problem in compatibility with the disease,’ ‘mental impasse,’ ‘facing social restrictions,’ and ‘concealment and social escapism.’ Conclusion: The findings demonstrated that older people with urinary incontinence experienced significant psychosocial pressures while living with this disorder, which affected their psychosocial well-being. Thus, paying attention to these psychosocial experiences while supporting and taking care of these patients can positively impact their psychosocial health and quality of life.